The potential role of value management in environmental impact assessment: a Maseru case study - Bowen, Paul; Hill, Richard; Mabote, Relebohile; Cattell, Keith; Edwards, Peter (University of the Free State, 2009)
English: Environmental impact assessment (EIA) studies are undertaken to assess the anticipated environmental impacts of proposed projects. Such studies typically address biophysical and socio-economic issues. Using a case study approach, the effectiveness of the EIA process adopted for a landfill project in Maseru, Lesotho, is reviewed. It was found that the Maseru environmental impact statement (EIS) was not fit for the purpose as it did not facilitate effective decision-making. This failure was to a large extent due to inadequate briefing by the client and ineffective study implementation and review procedures. It is proposed that value management (VM), a value-adding technique mainly applied in the manufacturing and construction industries, could improve the effectiveness of EIA.

Afrikaans: Studies oor omgewingsimpakwaardering is gedoen om die geantisipeerde omgewingsimpak van voorgestelde projekte te skat. Sulke studies spreek biofisiese en sosio-ekonomiese sake aan. ’n Gevallestudie oor die effektiwiteit van die omgewingsimpakwaardering van ’n stortingsterreinprojek in Maseru, Lesotho is gedoen. Daar is gevind dat die Maseru omgewingsimpakverslag nie gepas was vir die doel omdat dit nie effektiewe besluitneming gefasiliteer het nie. Hierdie mislukking was grootliks toe te skryf aan onvoldoende instruksies deur die kliënt en oneffektiewe studie implementering en oorsigprosedures. Daar word voorgestel dat waardebestuur, ’n waardetoevoegingstegniek grootliks toegepas in die vervaardigings- en konstruksie-industrieë, die effektiwiteit van omgewingsimpakwaardering kan verbeter.
Keywords: Value management; Environmental impact assessment; Sustainability; Infrastructure; Planning and design